Aggregate Information and the Role of Monetary Policy in an Open Economy - Kimbrough, Kent P. (Journal of Political Economy, 1984)
A model of a small open economy in which agents trade in local goods markets and an economy-wide asset market is developed. Purchasing-power parity is assumed to hold at the aggregate level. However, because of local deviations from purchasing-power parity, agents possess differential information. Using this framework, it is shown that when the exchange rate is flexible monetary policy can influence the distribution of real output by altering the information content of the exchange rate. However, when monetary policy is committed to fixing the exchange rate (by a feedback rule) the distribution of real output is independent of the particular exchange rate rule chosen. The stability of real output under the two regimes is compared, and it is demonstrated that regardless of the stability of domestic monetary policy a flexible exchange rate regime is superior in this respect. Possible qualifications and extensions of these results are also discussed.